Serum proteome analysis of vivax malaria: An insight into the disease pathogenesis and host immune response - Ray, Sandipan; Kamath, Karthik S.; Srivastava, Rajneesh; Raghu, Dinesh; Gollapalli, Kishore; Jain, Rekha; Gupta, Shipra V.; Ray, Sayantan; Taur, Santosh; Dhali, Snigdha; Gogtay, Nithya; Thatte, Urmila; et al. (Journal of proteomics, 2012)
Vivax malaria is the most widely distributed human malaria resulting in 80–300million clinical cases every year. It causes severe infection and mortality but is generally regarded as a benign disease and has not been investigated in detail. The present study aimed to perform human serum proteome analysis in a malaria endemic area in India to identify potential serum biomarkers for vivax malaria and understand host response. The proteomic analysis was performed on 16 age and gender matched subjects (vivax patients and control) in duplicate. Protein extraction protocols were optimized for large coverage of the serum proteome and to obtain high-resolution data. Identification of 67 differentially expressed and statistically significant (Student's t-test; p<0.05) protein spots was established by MALDI-TOF/TOF mass spectrometry. Many of the identified proteins such as apolipoprotein A and E, serum amyloid A and P, haptoglobin, ceruloplasmin, and hemopexin are interesting from a diagnostic point of view and could further be studied as potential serum biomarkers. The differentially expressed serum proteins in vivax malaria identified in this study were subjected to functional pathway analysis using multiple software, including Ingenuity Pathway Analysis (IPA), Protein ANalysis THrough Evolutionary Relationships (PANTHER) and Database for Annotation, Visualization and Integrated Discovery (DAVID) functional annotation tool for better understanding of the biological context of the identified proteins, their involvement in various physiological pathways and association with disease pathogenesis. Functional pathway analysis of the differentially expressed proteins suggested the modulation of multiple vital physiological pathways, including acute phase response signaling, complement and coagulation cascades, hemostasis and vitamin D metabolism pathway due to this parasitic infection. This article is part of a Special Issue entitled: Proteomics: The clinical link. [Display omitted] ► Alteration in serum proteome in vivax malaria was investigated. ► Classical 2DE and 2D-DIGE were implicated for serum proteome profiling. ► 31 differentially expressed serum proteins were identified using MALDI TOF/TOF MS. ► Identified proteins are involved in vital physiological pathways. ► Few identified proteins could further be studied as potential serum biomarkers.